SGLT2 inhibitors for primary and secondary prevention of cardiovascular and renal outcomes in type 2 diabetes: a systematic review and meta-analysis of cardiovascular outcome trials. Issue 10166 (5th January 2019) - Zelniker, Thomas A; Wiviott, Stephen D; Raz, Itamar; Im, Kyungah; Goodrich, Erica L; Bonaca, Marc P; Mosenzon, Ofri; Kato, Eri T; Cahn, Avivit; Furtado, Remo H M; Bhatt, Deepak L; Leiter, Lawrence A; et al.
Summary: Background: The magnitude of effect of sodium-glucose cotransporter-2 inhibitors (SGLT2i) on specific cardiovascular and renal outcomes and whether heterogeneity is based on key baseline characteristics remains undefined. Methods: We did a systematic review and meta-analysis of randomised, placebo-controlled, cardiovascular outcome trials of SGLT2i in patients with type 2 diabetes. We searched PubMed and Embase for trials published up to Sept 24, 2018. Data search and extraction were completed with a standardised data form and any discrepancies were resolved by consensus. Efficacy outcomes included major adverse cardiovascular events (myocardial infarction, stroke, or cardiovascular death), the composite of cardiovascular death or hospitalisation for heart failure, and progression of renal disease. Hazard ratios (HRs) with 95% CIs were pooled across trials, and efficacy outcomes were stratified by baseline presence of atherosclerotic cardiovascular disease, heart failure, and degree of renal function. Findings: We included data from three identified trials and 34 322 patients (60·2% with established atherosclerotic cardiovascular disease), with 3342 major adverse cardiovascular events, 2028 cardiovascular deaths or hospitalisation sfor heart failure events, and 766 renal composite outcomes. SGLT2i reduced major adverse cardiovascular events by 11% (HR 0·89 [95% CI 0·83–0·96], p=0·0014), with benefit only seen in patients with atherosclerotic cardiovascular disease (0·86 [0·80–0·93]) and not in those without (1·00 [0·87–1·16], p for interaction=0·0501). SGLT2i reduced the risk of cardiovascular death or hospitalisation for heart failure by 23% (0·77 [0·71–0·84], p<0·0001), with a similar benefit in patients with and without atherosclerotic cardiovascular disease and with and without a history of heart failure. SGLT2i reduced the risk of progression of renal disease by 45% (0·55 [0·48–0·64], p<0·0001), with a similar benefit in those with and without atherosclerotic cardiovascular disease. The magnitude of benefit of SGLT2i varied with baseline renal function, with greater reductions in hospitalisations for heart failure (p for interaction=0·0073) and lesser reductions in progression of renal disease (p for interaction=0·0258) in patients with more severe kidney disease at baseline. Interpretation: SGLT2i have moderate benefits on atherosclerotic major adverse cardiovascular events that seem confined to patients with established atherosclerotic cardiovascular disease. However, they have robust benefits on reducing hospitalisation for heart failure and progression of renal disease regardless of existing atherosclerotic cardiovascular disease or a history of heart failure. Funding: None.